Pelaksanaan Tahfidz Al-Qur’an di Pondok Pesantren Shuffah Al Fatah Tanjungsari - Diana Putri Nuur Muslimah; Delis Sri Maryati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Memorizing the Qur’an is a very honourable act. Since the Qur’an was revealed, an increasing number of people have committed it to memory. They pay special attention to the Qur’an, devoting their time, energy, and thoughts to preserving it. But it’s not simple to memorize the Qur’an. It is very important to prepare well because there will be challenges that arise during the memorization process. The case study technique serves as the methodological basic for this qualitative investigation. Facts, symptoms, issues, and events that naturally arise in the field are anticipated to be analysed and interpreted using the qualitative approach Overall, Shuffah Al Fatah Islamic Boarding School’s Al-Qur’an memorization curriculum has demonstrated extensive success. This program not only produces individuals who memorize the Qur’an, but also shapes the character of students who excel in spiritual, intellectual, and social aspects. This success confirms that an educational model that combines mastery of religious knowledge with character building in a supportive environment can produce human resources with noble character and a positive role in society. The results of the study indicate that four main management roles are used to administer Al-Qur’an memorization instruction in Shuffah Al Fatah Islamic Boarding School